English Language Teachers' Perceptions and Practice of Critical Thinking in Classrooms - Bhim Lal Bhandari (Mauve Journal De Leardu, 2024)
This paper discovers English language teachers' perspectives and practice of critical thinking in classrooms. Information was gathered through four English language teachers’ semi-structured interviews exposed purposively selected from four community schools in the Rupandehi, Nepal. The findings indicate that while teachers possess a positive perception of CT and have relevant classroom experiences, several barriers hinder the full integration of critical thinking into their pedagogical practices. These challenges include devotion to conventional teaching methods, students’ limited linguistic proficiency, a rigid curriculum, insufficient resources and lack of institutional support, deep-rooted beliefs and teaching experiences, and a lack of professional development opportunities for teachers. The study's implications can offer valuable insights into the perspectives and practices of secondary English language educators about the development of critical thinking in language instruction.